An interesting project of saçaklizade aiming at "improvement" religious life of ottoman public in reform age: "Invitation and forcing to knowledge and action - Gel, Mehmet (Turkish Historical Society e-magaza@ttk.org.tr, 2018)
In this study, ideas in two treatises tided Mektüb ila ulemdi'l-bildd andNasihatu'l-ultma of Saaklizade Muhammed el-Mar'a§i (death 1732), a scholar from rural areas lived in 17th and 18th centuries, are examined. Saaklizade mentions striking claims that religion was pushed back in Ottoman society and that scholars and rulers did not put sufficient effort in "inviting" and "enforcing" public to religious affairs. In addidon, he asserts that it was required to revive sharia (ihya), renew religion (tecdid) and improve religious affairs of Muslim public (lslah) in that age as a more striking matter. No doubt that these ideas are very important in terms of both scientific mindset of Saçaklizade, as a scholar, and religious-social history of Ottomans and deserve an analysis. © 2018 Elsevier B.V., All rights reserved.
Islâhat çağinda osmanli halkinin dini hayatini islah a yönelik saçaklizâde'nin ilginç bir önerisi: " Ilim ve 'amele da'vet ve icbar
Keywords: 18th Century; Improvement; Public; Reform; Religious Affairs; Revival; Saçaklizade; Scholars